Induced membrane technique combined with two-stage internal fixation for the treatment of tibial osteomyelitis defects. Issue 7 (July 2017) - Luo, Fei; Wang, Xiaohua; Wang, Shulin; Fu, Jingshu; Xie, Zhao
Abstract: Introduction: The purpose of this study was to observe the effects of induced membrane technique combined with two-stage internal fixation in the treatment of tibial osteomyelitis defects. Methods: A retrospective analyses for 67 cases of tibialosteomyelitis defects were admitted to our department between September 2012 to February 2015, which were treated with induced membrane technique. At the first stage, implanted with a PMMA cement spacer in the defects after radical debridement and fixed with reconstructive locked plate. Bone grafting and exchanged the plate with intramedullary nail at the second stage. Results: In current study, all patients were followed up for 18–35 months. Sixty-six patients achieved bone union with the average radiographic and clinical healing times of 5.55 ± 2.19 and 7.45 ± 1.69 months, respectively. Seven patients required a second debridement before grafting, while four patients experienced a recurrence of infection or a relapse following second stage treatment. Twelve patients experienced either knee or ankle dysfunctions and 2 patients faced delayed wound healing. Donor site complications includes pain and infection were found in 7 and 3 patients, respectively with delayed stress fracture in 1 patient only. Conclusions: Induced membrane technique for the treatment of tibial osteomyelitis defects, seems a reliable method. The use of reconstructive locked plate as a temporary internal fixation at the first stage and exchanged with intramedullary nail at the second stage, potentially achieves good clinical efficacy. Care should be taken to restore the joint function especially in distal tibia.